Analysis of Mortality in Patients Treated With Phenylephrine in Septic Shock. (February 2023) - Patel, Vishal V.; Sullivan, Jesse B.; Cavanaugh, Joseph
Background: Phenylephrine is a selective α1 -receptor agonist used to manage shock. Current guidelines for septic shock recommend limited utilization of phenylephrine due to the lack of evidence available. This deviates from previous guidelines, which had recommendations of when utilization may be appropriate. Objective: The primary objective of this study was to evaluate mortality in patients receiving phenylephrine for the management of septic shock. Methods: This was a retrospective chart review from September 2015 to September 2017 evaluating all adult patients admitted to an intensive care unit (ICU) on vasopressors for management of septic shock. Patients were divided into 2 groups, those treated with phenylephrine and those treated without phenylephrine. The primary outcome was mortality. Secondary objectives included days on vasopressors and ICU length of stay. Two subgroup analyses were performed: 1 for phenylephrine as first-line therapy and 1 for patients with tachycardia at initiation of vasopressors. Patients started on phenylephrine for salvage therapy were excluded from this study. Results: 499 patients enrolled in the study. 148 (32%) were enrolled in the phenylephrine group. Phenylephrine was associated with an increase in mortality (56% vs 41%; p = 0.003). There was no difference in the days on vasopressors or ICU length of stay. Patients who had ongoing tachycardia were associated with increased mortality with phenylephrine (54% vs 36%, p = 0.02). There was no difference in mortality when phenylephrine was started as the initial vasopressor. Conclusion: Utilization of phenylephrine in septic shock patients, especially those with ongoing tachycardia, was associated with an increased rate of mortality.